قياس الكفاءة النسبية للقطاع المصرفي باستخدام نموذج تحليل مغلف البياناتDEA (دراسة مقارنة بين المصارف السورية والمصارف اللبنانية) - العمار رضوان; طه لارا (Latakia University Journal - Economic and Legal Sciences Series, 2018)
قدم هذا البحث دراسة تفصيلية للكفاءة النسبية للقطاع المصرفي لـ 18 مصرف تجاري (9 منها مصارف سورية والأخرى مصارف لبنانية) باستخدام نموذج تحليل مغلف البيانات DEA خلال عام 2010، وشملت الدراسة تحليل مجموعة من العوامل المؤثرة على كفاءة القطاع المصرفي والمتمثلة بـ حجم أصول المصرف والربحية والسيولة، وقد توصل الباحث إلى النتائج التالية: (1) لا يوجد فرق معنوي في كفاءة كل من المصارف السورية واللبنانية. (2) هناك علاقة طردية بين الكفاءة وبين حجم أصول المصرف والربحية وعدم وجود علاقة ارتباطية بين الكفاءة والسيولة. This paper presents a detailed study of the relative efficiency of the banking sector’s 18 commercial banks (9 of which are Syrian banks and the other are Lebanese banks) by using a data envelopment analysis model (DEA) in 2010. The study includes analysis of the factors affecting the efficiency of the banking sector, represented by the size of bank assets, the profitability and the liquidity. This paper has achieved a set of results which are: (1) there was no significant difference in the efficiency between the Syrian and Lebanese banks. (2) There is a direct correlation between efficiency and the size of bank assets and the profitability and there is not correlation between efficiency and liquidity.